Microbial Community Structure in the Rhizosphere of Rice Plants - Breidenbach, Björn; Pump, Judith; Dumont, Marc G. (Frontiers in Microbiology, 2016)
The microbial community in the rhizosphere environment is critical for the health of land plants and the processing of soil organic matter. The objective of this study was to determine the extent to which rice plants shape the microbial community in rice field soil over the course of a growing season. Rice (Oryza sativa) was cultivated under greenhouse conditions in rice field soil from Vercelli, Italy and the microbial community in the rhizosphere of planted soil microcosms was characterized at four plant growth stages using quantitative PCR and 16S rRNA gene pyrotag analysis and compared to that of unplanted bulk soil. The abundances of 16S rRNA genes in the rice rhizosphere were on average twice that of unplanted bulk soil, indicating a stimulation of microbial growth in the rhizosphere. Soil environment type (i.e. rhizosphere versus bulk soil) had a greater effect on the community structure than did time (e.g. plant growth stage). Numerous phyla were affected by the presence of rice plants, but the strongest effects were observed for Gemmatimonadetes, Proteobacteria and Verrucomicrobia. With respect to functional groups of microorganisms, potential iron reducers (e.g. Geobacter, Anaeromyxobacter) and fermenters (e.g. Clostridiaceae, Opitutaceae) were notably enriched in the rhizosphere environment. A Herbaspirillum species was always more abundant in the rhizosphere than bulk soil and was enriched in the rhizosphere during the early stage of plant growth.